Causes of non-useful Papanicolaou smear in two health areas. Cienfuegos, 2005. - Miryam González González del Pino; Mayrim Hernández González (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
Background: Cervicouterine cancer represents 10 % of all types of cancer, and it is one of the three main death causes in women. Objectives: to determine the factors that may influence in the diagnosis of non-useful Papanicolaou smear in health areas II and III of Cienfuegos municipality, Cuba. Method: An ambispective analytic study was carried out in the second semester of the year 2005, in Cienfuegos municipality, Cuba. 122 non-useful Papanicolaou smear from health areas II and III were collected and those carrier women of the above mentioned samples were dated to repeat the test. The variables were; requisites and conditions to perform the test, visualization of the cervix and presence of vaginal sepsis. Results: An inadequated sample taking was observed in 93 patients (76,2 %), as well as the bad conditions of the place where the samples were taken. There was also instrumentation deficiency. The interview in more than 50 % of women was not the adequate one. Conclusions: Yet, existing an acceptable index of non useful Papanicolaou smear in Cienfuegos province, the program to detect cervicouterine cancer confront difficulties in its application and results.